Experience capitalization: Learning from farmer organisations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
This report comprises 13 case stories produced through the Experience Capitalization project implemented by CTA in different parts of the world. These cases are from farmer organisations working in East Africa: the Uganda National Farmers Federation, the Kenya National Farmers Federation, the Kenya Livestock Producers Association, MVIWATA in Tanzania, and the East Africa Farmers Federation. The cases provide an update on development projects aimed at farmer organisations in East Africa, and a first-hand view of their challenges and successes.